Gambaran Tinjauan Pelepasan Informasi Rekam Medis dalam Menjamin Aspek Hukum Kerahasiaan Rekam Medis di RSUD Haji Makassar - Patanduk, Marcilya Sheren; Mikawati, Mikawati; Putri, Rosana Dwiyanti; Malik, Muhammad Zukri (Jurnal Persada Husada Indonesia, 2024)
Medical records are confidential documents so that the release of Medical Record information must refer to the applicable procedures and in accordance with the regulations of the Minister of Health so that the legal aspects of confidentiality are guaranteed. Objective: to determine the description and identification of the consent given in ensuring the legal aspects of the confidentiality of Medical Records. Methodology: the research method used in this study is a descriptive qualitative approach that aims to identify the description and consent for the release of medical information in ensuring the legal aspects of the confidentiality of patient medical records. Results: based on the results of the study at the Haji Makassar Regional General Hospital for the established standard procedures, the legal aspects of confidentiality have been guaranteed, but there are still requirements that have been listed in the SOP that have not been formalized, namely the patient's permit or power of attorney. Conclusion: at the Haji Makassar Regional General Hospital regarding the release of patient medical information, it is still necessary to conduct re-socialization regarding the procedure for releasing patient medical information, so that all requirements that have been set in the SOP can be realized more optimally.